PENGARUH WAKTU TUNGGU PEMERIKSAAN LABORATORIUM TERHADAP KEPUTUSAN TERAPI PADA PASIEN RAWAT INAP - , Margaretha Mulyono; , Prof.dr.Iwan Dwiprahasto,M.Med,Se,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Fast and accurate lab test is very critical to clinicians in establishing medical diagnosis. Any delay in presenting lab result may compromise patient care plan and pose higher risk as a result of delayed treatment. Lab turnaround time is probably related to the attitudes of lab staff or some interruption in the process. Objective: The purpose of this study is to evaluate the influence of laboratory tests turnaround time on treatment/clinical decision of inpatients and to identify any factors contributing to laboratory tests turnaround time. Method: This research used a mixed-method study design with sequential quantitative-qualitative approach. The quantitative research applied a descriptive cross-sectional survey with sample size up to all obtained sample which were selected consecutively during the period of lab tests research. Qualitative research used semi-structured interview with lab and nursing staffs. Lab staffs sample were selected using criterion sampling while nursing staffs sample selected using maximum variation sampling. Sampling was done until data saturation occurs. Results and Discussion: The average of total turnaround time of lab tests obtained from phlebotomy procedure at inpatient unit until the time of the clinician making treatment instruction is 309,00 minutes. The longest time expended in the process is between the lab result received by inpatient unit to the time clinician made treatment instruction with the average of 195,00 minutes. It happened due to some non urgent results that were reported to the clinician on the next visit. Interruption duration to the lab staff is about 1 minute but interfere with lab staffs concentrations and prone to an error in measuring, recording and interpretating the test result. Conclusion: Lab turnaround time of Dr. OEN SOLO BARU Hospital fall far beyond the limit as provisioned in the Hospital Minimum Service Standard issued by the Ministry of Health of Indonesia. Therefore, there is a need to establish a turnaround time standart, promptly report laboratory result to the clinician by telephone, and established an effective job division among laboratory staffs .